Why peace endures: an analysis of post-conflict stabilisation. (22nd March 2017) - Caplan, Richard; Hoeffler, Anke
Abstract: This article is concerned with explaining why peace endures in countries that have experienced a civil armed conflict. We use a mixed methods approach by evaluating six case studies (Burundi, East Timor, El Salvador, Liberia, Nepal, Sierra Leone) and survival analysis that allows us to consider 205 peace episodes since 1990. We find that it is difficult to explain why peace endures using statistical analysis but there is some indication that conflict termination is important in post-conflict stabilisation: negotiated settlements are more likely to break down than military victories. We also consider the impact of UN peacekeeping operations on the duration of peace but find little evidence of their contribution. However, in situations where UN peacekeeping operations are deployed in support of negotiated settlements they do seem to contribute to peace stabilisation.